Предмет: Алгебра,
автор: yanasubbotina
Помогите!!! Срочно!!! Упростите выражение:а) (3х+у)(2х-5у)-6(х-у)2
б)(-2х3у)3 х (-5х2у)2
Ответы
Автор ответа:
2
а)=6х²-15ху+2ху-5у²-6х²+12ху-6у²=-11у²-ху
б)=-8*x^9*y^3*25*x^4*y^2 = -200x^13y^5
б)=-8*x^9*y^3*25*x^4*y^2 = -200x^13y^5
yanasubbotina:
Спасибо)
Похожие вопросы
Предмет: Русский язык,
автор: MAkSS112
Предмет: Русский язык,
автор: эльмирапетросян
Предмет: Русский язык,
автор: timon201
Предмет: Математика,
автор: Aziz333
Предмет: Алгебра,
автор: machilova10